Structural Diversity in Luminescent MOFs Containing a Bent Electron‐rich Dicarboxylate Linker and a Flexible Capping Ligand: Selective Detection of 4‐Nitroaniline in Water - Chakraborty, G.; Das, Prasenjit; Mandal, S.K. (Wiley Online Library, 2019)
A combination of a bent bis(naphthalene) and hydroxy‐based dicarboxylate linker and a flexible bis(tridentate)polypyridyl ligand has been employed to self‐assemble with two different d10 metal centers, ZnII and CdII, to form structurally diversified luminescent metal–organic frameworks, [Zn2(tpbn)(mbhna)2(H2O)2]⋅4 H2O⋅1.5DMF (1) and {[Cd2(tpbn)(mbhna)2]⋅2DMF}n (2), respectively (where, tpbn=N,N′,N′′,N′′′‐tetrakis(pyridine‐2‐ylmethyl)butane‐1,4‐diamine and H2mbhna=4,4′‐methylene‐bis[3‐hydroxy‐2‐naphthalene carboxylic acid]). Both 1 and 2 are characterized and analyzed by various analytical techniques including single‐crystal X‐ray diffractometry. Their excellent emissive nature is studied in different solvents and further utilized to selectively detect aromatic amines, particularly 4‐nitroaniline in water with detection limits at sub‐ppm level. The difference in sensing activity of 1 and 2 toward 4‐NA is corroborated well with their structures. The mechanism of action has been established through Stern–Volmer plot, spectral overlap, time‐resolved lifetime studies and HOMO–LUMO energy calculations. In addition, 1 and 2 are found to be recyclable and display good stability after sensing experiments.
Keywords: Fluorescence sensing; Luminescence; Metal–organic frameworks; 4-nitroaniline